2016
DOI: 10.1063/1.4971830
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs tunnel FET with sub-nanometer EOT and sub-60 mV/dec sub-threshold swing at room temperature

Abstract: InGaAs homojunction Tunnel FET devices are demonstrated with sub-60 mV/dec Sub-threshold Swing (SS) measured in DC. A 54 mV/dec SS is achieved at 100 pA/lm over a drain voltage range of 0.2-0.5 V. The SS remains sub-60 mV/dec over 1.5 orders of magnitude of current at room temperature. Trap-Assisted Tunneling (TAT) is found to be negligible in the device evidenced by low temperature dependence of the transfer characteristics. Equivalent Oxide Thickness (EOT) is found to play the major role in achieving sub-60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…Device A and B are compared to TFETs from other publications in Figure 4 (b). Even if Device A is limited by the strong source depletion it still reaches approximately 40% lower S MIN compared to other III-V based TFETs [10,21,[25][26][27][28][29] at drain current levels that are approximately two orders of magnitude larger than Si-based TFETs [7]. Output data from Device A, B, and C is shown in Figure 5.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Device A and B are compared to TFETs from other publications in Figure 4 (b). Even if Device A is limited by the strong source depletion it still reaches approximately 40% lower S MIN compared to other III-V based TFETs [10,21,[25][26][27][28][29] at drain current levels that are approximately two orders of magnitude larger than Si-based TFETs [7]. Output data from Device A, B, and C is shown in Figure 5.…”
Section: Resultsmentioning
confidence: 97%
“…So far, the impact of source doping on the performance of these TFETs has not been studied. Previous studies, based on TFETs with other material systems [21,25,38], have demonstrated the importance of this parameter. Based on experimental data from devices with the nominally same heterojunction but with different doping levels, we here study the impact of source doping on the overall performance of vertical InAs/InGaAsSb/GaSb nanowire TFETs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An oxide/Ga x In 1− x As interface is frequently found as part of various device components (e.g., metal–oxide–semiconductor (MOS) high electron mobility transistor, structure, and IR detectors) currently used in electronics and in the design of many a potential future device (e.g., III–V MOS field‐effect transistor, and tunnel field‐effect transistor) . However, oxide/Ga x In 1− x As interfaces are usually considered as nonoptimized, adversely affecting the device performance: namely, they contain a high density of material defects that cause electronic defect states in the band‐gap area (gap states), which further increase the leakage current, nonradiative recombination, and Fermi‐level pinning, for example.…”
Section: Introductionmentioning
confidence: 99%